1983
DOI: 10.2136/sssaj1983.03615995004700060025x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Genesis in a Natrargid‐Haplargid Complex in Northern Montana

Abstract: Classical theory of the genesis of Natargids (solonetz) involves the upward movement of sodium from a water table. Examination of 24 pedons representing four Soil Series developed in glacial till on the Northern Great Plains (Montana) suggests that Natrargids (solonetz and solodized‐solonetz) and Haplargids (soloth) can develop in the absence of a water table. The four soils occur as a complex on “panspot” rangeland with the soloth and solodized‐solonetz on microknolls and the solonetz in microdepressions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Also termed alkalization, this occurs when soils subject to salinization are drained (Munn & Boehm, ). The excess soluble salts are leached out, the colloids because of the influence of Na become dispersed, and a strongly alkaline reaction develops.…”
Section: Resultsmentioning
confidence: 99%
“…Also termed alkalization, this occurs when soils subject to salinization are drained (Munn & Boehm, ). The excess soluble salts are leached out, the colloids because of the influence of Na become dispersed, and a strongly alkaline reaction develops.…”
Section: Resultsmentioning
confidence: 99%
“…Pedon G may have been affected by the ditch as well, even though it is 50 m below it Pedons F and Gwererelatively shallow to the 2Cr'horizon contact (<160 cm). The relatively shallow soil depth may explain the occurance of high SAR values in pedons F and G at shallower depths than in other profiles where the 2Cr horizons occured at depths of> 200 cm (Munn and Boehm, 1983).…”
Section: Accumulation Of Materialsmentioning
confidence: 78%
“…For example, smectite in salt-affected soils in North America would experience degradation due to the impact of high salt and soda content [10]. Smectite deformed in the surface horizons of solonetzic soils in Montana [11]. In these existing studies, the impact of high salinity on the formation of smectite was reported, whereas it was not reported anywhere on how the different salt content would influence the formation of smectite.…”
Section: Introductionmentioning
confidence: 99%